Blood Glucose and Urea Levels of Male Bali Cattle Fattened With Complete Feed Containing Fish Meal As a Protein Source - Ferdy Anin; Paulus Klau Tahuk; Oktovianus Rafael Nahak; Gerson Frans Bira (Universitas Veteran Bangun Nusantara, 2022)
This research was conducted in 2021 for 3 months at the Faculty of Agriculture, University of Timor. The purpose of this study was to determine the blood glucose and urea levels of male Bali cattle fattened with complete feed containing fish meal as a protein source. This research method uses a completely randomized design (CRD) with 3 treatments and 5 replications so that there are 15 experimental units with treatment given T1; natural grass 30% + milled corn 42% + rice bran 13% + pollard bran 11% + fish meal 4%, T2: natural grass 42% + milled corn 42% + rice bran 9% + pollard bran 11% + fish meal 8 %, T3: natural grass 30% + milled corn 42% + rice bran 5% + pollard bran 11% + fish meal 12%. The variables observed in this study were blood glucose and blood urea levels of male Bali cattle with a time of 0 hours before feeding, 2 hours, 4 hours, and 6 hours after feeding. The data obtained were tabulated and then analyzed by Analysis of Variance (ANOVA) according to a completely randomized design procedure (CRD) using SPSS version 19.0. The results of this study showed that the use of complete feed containing fish meal as a protein source was not significantly different. Blood glucose levels (mg/dL) for each treatment were T1: 73.23±3.50, T2: 76.24±6.21, T3: 71.94±2.54; Blood urea levels (mg/dL) of male Bali cattle for each treatment were T1: 40.23±3.51, T2: 40.95±2.04, T3: 39.67±1.83. It was concluded that giving a complete feed containing fish meal as a protein source gave the same effect for all treatments and resulted in blood glucose and urea levels of fattened male Bali cattle in the normal range.